Different living environments drive deterministic microbial community assemblages in the gut of Alpine musk deer (Moschus chrysogaster) - Zhang, Zhirong; Ding, Mengqi; Sun, Yujiao; Khattak, Romaan Hayat; Chen, Junda; Teng, Liwei; Liu, Zhensheng (Frontiers in Microbiology, 2023)
Substantial variation in the environment directly causes a remodeling of the colonized gut microbiota controlling community diversity and functions in the host to tune-up their adaptive states. However, the mechanisms of microbial community assembly in response to environmental changes remains unclear, especially in endangered ruminants. In this study, we analyzed the microbial communities of 37 fecal samples collected from captive and wild Alpine musk deer (Moschus chrysogaster) to characterize the complexity and assembly processes using 16S rRNA gene sequencing. We found significantly different diversity and compositions of gut microbiota among both groups associated with different living environments. Heterogeneous selection was the predominant factor regulating the gut microbiota community under similar climatic conditions, indicating that microbial community assembly was largely driven by deterministic mechanisms. The species co-occurrence network showed complex and tight connections with a higher positive correlation in the wild environment. Moreover, the captive group exhibited significant differences in chemo heterotrophy and fermentation compared with the wild group, but the opposite was observed in animal parasites or symbionts, which might be closely related to diet, energy supply, and healthcare of the animals. This study provides a framework basis and new insights into understanding gut microbiota in different environments.